Polypyrrole/graphene composite films synthesized via potentiostatic deposition - Lim Y.S.; Tan Y.P.; Lim H.N.; Tan W.T.; Mahnaz M.A.; Talib Z.A.; Huang N.M.; Kassim A.; Yarmo M.A. (2024)
Indexed by WOS/ Scopus